FEATURES OF TEACHING HYPERACTIVE CHILDREN IN PRIMARY SCHOOL (Ustozlar uchun, 2024)
Annotation. The article analyzes the fcaturcs in ieaching ofhypcractive pupils, discusses the prcvention and correcion of diicultics in teaching hypcracive children in primary school.